The complete mitochondrial genome of the golden snapper Lutjanus johnii (Perciformes: Lutjanidae). (3rd March 2016) - Taillebois, Laura; Crook, David; Saunders, Thor; Ovenden, Jennifer
Abstract: We describe the complete mitochondrial genome of the golden snapper Lutjanus johnii . It was assembled from approximately 1.4 million reads produced by Ion Torrent next generation sequencing. The complete genome was 16, 596 bp in length consisting of 13 protein-coding regions, 22 tRNA, 12S and 16S rRNA as well as two non-coding regions. The A+T base content (52.8%) is similar to other teleosts.